From Constantine to Julian : pagan and Byzantine views ; a source history - Lieu, Samuel N. C.; Montserrat, Dominic, 1964- (Routledge, 1996)
Provides students with important source material covering an age of major transition in Europe - the establishment of Rome as a Christian empire. Most of the material was previously unavailable in English.